Development of a Structured Machinery MaintenanceInspection Checklist in a New High-Capacity Production Line - Hassan, Ahmad Firdause Emir; Amir Haziq Abdul Razak,; Aqeela Bahijah Majudin, (Progress in Engineering Application and Technology, 2026)
The implementation of new high-capacity production lines often emphasizes efficiency and output, while maintenance-related safety risks may receive less attention, particularly during early operational stages. At Kilang Makanan Mamee Sdn. Bhd., Subang, the absence of a structured and machine-specific maintenance inspection checklist for critical equipment highlighted the need for a systematic safety-based approach. This study aims to develop and propose a structured machinery maintenance safety inspection checklist to enhance worker safety and support consistent hazard identification. Hazard Identification, Risk Assessment, and Risk Control (HIRARC) analysis was conducted to identify critical equipment with higher maintenance-related risks. The methodology involved site walkthrough observations, document reviews, and informal discussions with safety, maintenance, and production personnel to understand actual maintenance practices and hazard exposure. Based on the findings, a safety-focused maintenance inspection checklist was developed, emphasizing practical applicability rather than machine performance evaluation. The results indicate that the developed checklist addresses key maintenance safety concerns, including mechanical hazards, thermal exposure, electrical risks, lockout–tagout (LOTO) readiness, safe access, and post-maintenance verification. Feedback from relevant departments confirmed that the checklist is clear, practical, and suitable for routine maintenance use. It is recommended that the checklist be formally adopted into maintenance procedures, periodically reviewed, and expanded to other critical machines to strengthen long-term maintenance safety practices.